2021
DOI: 10.12968/live.2021.26.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Control of mastitis in dairy sheep and goats

Abstract: Clinical mastitis is much less common in dairy sheep and goats than in cattle, but it is still a major cause of loss and impaired welfare. Subclinical mastitis rates range from 5–30%, but it is a significant cause of lost production and impaired milk quality. Gram-positive bacteria, in particular Staphylococcus aureus and coagulase-negative staphylococci, and contagious modes of transmission predominate. Diagnosis is complicated by higher somatic cell counts (SCC) even in uninfected udders, particular in goats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…The aforementioned workers attributed their causes to the suckling lambs that play an important role in transmitting infection because they carry the pathogen in their nasopharynx (2,15). However, the outcome of the present work is in accordance with those authors Omaleki et al (15) and Van den et al (19), who isolated and identified other species of Mannheamia (M. haemolytica, M. ruminalis and M. glucosida) from multiple cases of acute mastitis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The aforementioned workers attributed their causes to the suckling lambs that play an important role in transmitting infection because they carry the pathogen in their nasopharynx (2,15). However, the outcome of the present work is in accordance with those authors Omaleki et al (15) and Van den et al (19), who isolated and identified other species of Mannheamia (M. haemolytica, M. ruminalis and M. glucosida) from multiple cases of acute mastitis.…”
Section: Discussionsupporting
confidence: 91%
“…Mastitis is regarded as an important productive disease contracting ranged-reared sheep with particular concern of those dairy and nursing ewes. Several studies have approved and confirmed the effective role of M. haemolytica as a primary and crucial etiology of mastitis in sheep which similar to those caused by Staphylococcus aureus, however, the infection percentages of the former microorganism are relatively higher (2,4,15). Consequently, the current work supports such type of mastitis in sheep of Mosul city.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Hassan and Yousif (6) found the 12.22% of subclinical mastitis in ewes in Al Anbar Province. Many articles showed that S. aureus is one of the most important bacteria causing mastitis in dairy animals including sheep (7,8). California mastitis test used as a quick field assay to determine subclinical mastitis of ewes and other animals, its Iraqi Journal of Veterinary Sciences, Vol.…”
Section: Introductionmentioning
confidence: 99%